Genomic, expression and functional analysis of genes from larval gut of the European corn borer, Ostrinia nubilalis (Hübner) - Khajuria, Chitvan (Kansas State University, 2010)
Genomic information for lepidopteran insects, particularly agricultural pest species, is very limited but urgently needed due to their economic importance and biodiversity. The huge economic losses ($ 1-2 billons / year) caused by the European corn borer (Ostrinia nubilalis, Hübner, ECB) makes this insect species one of the major pests of corn in the United States and western world. Management of ECB by conventional methods is limited but has had a great success by transgenic Bt (Bacillus thuringiensis) corn, which targets insect gut. However, the widespread use of Bt corn may lead to the development of Bt resistance in ECB. Knowledge of genes expressed in the insect gut is considered crucial for understanding basic physiology of food digestion, their interactions with Bt toxins and pathogens, and for discovering new targets for pest management. A large database of 15,000 expressed sequence tags (ESTs) was established from the ECB larval gut. To our knowledge, this database represents the largest gut-specific EST database from a lepidopteran pest. Analysis of 10 aminopeptidase-like genes between Cry1Ab–resistant and –susceptible ECB larvae revealed that aminopeptidase P-like (OnAPP) gene is a strong candidate for its role in Bt toxicity and resistance. The RNA interference mediated reduction in the transcript level of OnAPP gene in ECB larvae resulted in their reduced susceptibily to Cry1Ab. Analysis of the chitinase-like gene (OnCht) revealed its essential role in regulating chitin content of peritrophic membrane (PM). Our results suggest that OnCht may influence food digestion, nutrient absorption or movement of digestive enzymes through the PM and can be an important target for insect management. We also identified and characterized six genes involved in the innate immune defense response in ECB and showed that the expression of these genes were induced when challenged with bacteria. In addition to these results, this research generated significant genomic information for the development of microarray from the larval gut of ECB. The establishment of the feeding-based RNA interference technique could potentially help in delivering dsRNA orally to ECB for high throughput screening of effective genes to be targeted for insect pest management.
Keywords: European corn borer; gut; Express sequence tag; Biology, Entomology (0353)